BOTRYTIS-INDUCED KINASE1, a plasma membrane-localized receptor-like protein kinase, is a negative regulator of phosphate homeostasis in Arabidopsis thaliana. Issue 1 (December 2016) - Zhang, Huijuan; Huang, Lei; Hong, Yongbo; Song, Fengming
Abstract Background Plants have evolved complex coordinated regulatory networks to cope with deficiency of phosphate (Pi) in their growth environment; however, the detailed molecular mechanisms that regulate Pi sensing and signaling pathways are not fully understood yet. We report here that the involvement of Arabidopsis BIK1, a plasma membrane-localized receptor-like protein kinase that plays critical role in immunity, in Pi starvation response. Results qRT-PCR analysis revealed that expression ofBIK1 was induced by Pi starvation and GUS staining indicated that theBIK1 promoter activity was detected in root, stem and leaf tissues of plants grown in Pi starvation condition, demonstrating thatBIK1 is responsive to Pi starvation stress. Thebik1 plants accumulated higher Pi content in root and leaf tissues and exhibited altered root architecture such as shorter primary roots, longer and more root hairs and lateral roots, as compared with those in the wild type plants, when grown under Pi sufficient and deficient conditions. Increased anthocyanin content and acid phosphatase activity, reduced accumulation of reactive oxygen species and downregulated expression of Pi starvation-induced genes includingPHR1, WRKY75, AT4, PHT1;2 andPHT1;4 were observed inbik1 plants grown under Pi deficient condition. Furthermore, the expression ofPHO2 was downregulated while the expression ofmiRNA399a andmiRNA399d, which target toPHO2, was upregulated inbik1 plants, compared to the wild type plants, when grown under Pi deficient condition. Conclusion Our results demonstrate thatBIK1 is a Pi starvation-responsive gene that functions as a negative regulator of Pi homeostasis in Arabidopsis.